PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS KETERAMPILAN METAKOGNISI PADA MATERI LAJU REAKSI - Nurmiati, Euis; Dahlan, Dahlan; Rudi, La (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2021)
This research is related to the development of student worksheets (LKPD) based on  metacognition  skills  in  one  of  the  Chemistry  learning  materials,  namely  the reaction  rate.  This  material  was  chosen  because  this  material  contains metacognition  skills  as  one  of  the  aspects  that  must  be  achieved  in  Core  Competencies (KI). Metacognition skills can help students become self-regulated learners  who  are  responsible  for  their  own  learning  progress  and  adapt  their learning strategies to achieve the demands of the assignment. The importance of LKPD based on metacognition skills is developed so that students understand how the  task  is  carried  out  and  monitor  their  own  learning  progress.  Therefore,  the student worksheet contains components of metacognition skills such as planning, monitoring  (monitoring),  evaluating  (evaluating),  and  revising  (revising).  The purpose  of  this  study  was  to  develop  metacognition-based  student  worksheets (LKPD) on the material on reaction rates. The type of research being carried out by researchers is research and development using the 4-D model, namely define, design, development, and disseminate stages. The instrument used was a content assessment  /  validation  sheet.  Furthermore,  the  second  data  is  related  to  a questionnaire  related  to  the  implementation  of  the  LKPD.  The  results  of  the questionnaire are as follows: (1) LKPD media 65.45%, (2) LKPD material 71.25%, (3) LKPD language 78%, and (4) LKPD metacognition skills 77.5% with average percentage -The mean of all scores is 73.05%.